Engine power limitation (EPL) to comply with EEXI requirements. study on an LPG tanker - Adrian Costache; Radu Bosoancă (Annals of "Dunărea de Jos" University of Galaţi: Fascicle XI Shipbuilding)
The study analyses the Energy Efficiency Existing Ship Index (EEXI), a regulation introduced by the International Maritime Organization (IMO) to enhance energy efficiency in maritime transport and reduce greenhouse gas emissions. Focusing on a semi-refrigerated LPG tanker, the research explores compliance strategies, including engine power limitation (EPL). The reduction of engine power by 24% resulted in a decrease in ship speed, meeting EEXI requirements with minimal impact on performance. Additionally, ship manoeuvrability was assessed through turning circle simulations before and after EPL. The findings confirmed that the vessel’s manoeuvrability remains within IMO standards, ensuring both efficiency and operational safety.